Representation of knowledge for a NASA stakeholder value model. Issue 5 (29th August 2019) - Clerkin, Joseph H.; Mesmer, Bryan L.
Abstract: A challenge in the representation of preferences for government stakeholders is the valuation of benefits. In for‐profit companies, benefits are typically calculated as the company's revenue, with centuries of literature supporting different estimations for the benefit of revenue. Government stakeholders are much more difficult to develop value models for because of the lack of benefit‐side valuation research. In its pursuit of understanding the theory of systems engineering, the NASA Systems Engineering Research Consortium has examined value models as mathematical representations of preferences, with a focus on NASA‐related stakeholders. This article leverages the Consortium work and develops an outline for a NASA stakeholder value model, based on NASA documentation, with key benefit attributes of knowledge, prestige, and the avoidance of catastrophes. The attribute of knowledge is specifically explored in this article. Knowledge‐related evidence from previous NASA missions are collected and analyzed. A discussion describes how such knowledge‐related evidence can be used to inform the systems engineer on preliminary, evidence‐based attribute and value relationships useful in value model formation. Future research avenues for knowledge‐focused benefits for value models are also discussed.